Menanamkan Nilai Pancasila Melalui Penguatan Pendidikan Karakter untuk Siswa Sekolah Dasar - Yutri Wahyuni (Pusat Riset dan Inovasi Nasional, 2024)
Embedding Pancasila Values Is Crucial for Indonesia's Future This study aims to investigate the policy of character education strengthening to realize Pancasila Students. The approach used in this research is a literature approach, with data collection methods in the form of books, literatures, and scientific journals. The results of the study show that the strengthening of character education in realizing Pancasila Students is essentially fostering the emergence of good human beings, who possess six main characteristics, namely critical thinking, creativity, independence, faith, piety towards God Almighty, noble morals, mutual cooperation, and global diversity, with the hope that students will have the ability to independently increase, use their knowledge, examine, internalize, and personalize character and moral values that can be realized in daily behavior.